Evaluation of dried skim milk, dried whey, and fat in pig starters - Stuart, J.G.; Koch, B.A.; Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Five starters were compared with a corn-soybean meal standard with 15% skim milk and 12% sugar. Rations containing dried skim milk or dried whey with 3 or 5% added edible fat also were compared. The rations were offered to suckling baby pigs from 2 to 4 weeks (phase 1) and again during 6 to 10 weeks of age (phase 2). During phase 1, neither feed intake nor total gain differed significantly. During phase 2 all rations produced similar weight gains and feed intake. Feed efficiency favored rations containing dried skim milk and 3 or 5% added fat. Rations containing more fat produced more efficient gains.
Swine Industry Day 1970 is known as Swine Day, 1970
Keywords: Swine; Dried skim milk; Dried whey; Fat